2009
DOI: 10.1063/1.3127525
|View full text |Cite
|
Sign up to set email alerts
|

Electric discharge caused by expanding armatures in flux compression generators

Abstract: Articles you may be interested inFast modeling of flux trapping cascaded explosively driven magnetic flux compression generators Rev. Sci. Instrum. 84, 014703 (2013); 10.1063/1.4775488 High power pulse compression using magnetic flux compression J. Appl. Phys. 111, 094508 (2012); 10.1063/1.4709749Fast-charging compact seed source for magnetic flux compression generators Rev.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…We used a Cordin 10-A framing camera at half a million frames per second to photograph the experiments. Other experimental details are elsewhere [37], [38]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used a Cordin 10-A framing camera at half a million frames per second to photograph the experiments. Other experimental details are elsewhere [37], [38]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently we experimentally demonstrated that the main factor that causes the initiation of the gas discharge in the FCG is not the electric field strength within the generator, but the explosive expansion of the armature that plays a dominant role in the formation of plasma and gas discharge initiation [11]. In this paper we present extended results of these studies.…”
Section: Introductionmentioning
confidence: 65%